2009
DOI: 10.1111/j.1442-9071.2008.01822.x
|View full text |Cite
|
Sign up to set email alerts
|

Imaging for neuro‐ophthalmic and orbital disease – a review

Abstract: A literature review was performed by content experts in neuro-ophthalmology and neuroradiology using a systematic English-language Medline search (1994)(1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008) limited to articles with relevance to neuro-ophthalmic and orbital imaging. The information covered in this review includes: (i) the basic mechanics, indications and contraindications for cranial and orbital computed tomography and magnetic resonance (MR) imaging; (ii) the util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 103 publications
(202 reference statements)
0
54
1
10
Order By: Relevance
“…15,16 DWI has been a complementary technique useful in the differential diagnosis of orbital pathologies such as orbital inflammatory syndrome, orbital lymphoid lesion, orbital cellulitis, acute optic nerve infarction, endophthalmitis, acute ischemic homonymous hemianopsia, indeterminate orbital masses, and optic neuritis. [18][19][20][21][22][23] Also, Politi et al 24 recorded the ADC of the vitreous humor in healthy subjects as part of a normative data collection for a larger study of orbital masses and found a mean vitreal ADC that is significantly lower than that in our results; the difference might be due to different techniques used in the studies.…”
Section: Discussioncontrasting
confidence: 54%
“…15,16 DWI has been a complementary technique useful in the differential diagnosis of orbital pathologies such as orbital inflammatory syndrome, orbital lymphoid lesion, orbital cellulitis, acute optic nerve infarction, endophthalmitis, acute ischemic homonymous hemianopsia, indeterminate orbital masses, and optic neuritis. [18][19][20][21][22][23] Also, Politi et al 24 recorded the ADC of the vitreous humor in healthy subjects as part of a normative data collection for a larger study of orbital masses and found a mean vitreal ADC that is significantly lower than that in our results; the difference might be due to different techniques used in the studies.…”
Section: Discussioncontrasting
confidence: 54%
“…In a review on brain and orbit imaging, Lee et al concluded that MRI is the procedure of choice for almost all neuro-ophthalmic indications, including cavernous sinus lesions. However, CT is superior to MRI in cases that require visualization of bone, calcifications or in emergent cases, as well as in patients who cannot undergo MRI [5]. Biopsy is technically difficult and is usually the last resort in patients with cavernous sinus lesions in whom the etiology cannot be determined by less invasive techniques [3].…”
Section: Discussionmentioning
confidence: 99%
“…These imaging tools are also valuable in evaluating the deep orbital structures behind the globe to define the full extent of the clinically evident infection, inflammation, or neoplasm, or in cases of blunt trauma. 18,19 CT is the workhorse in imaging evaluation for calcification, infection, integrity of the implants, and orbital reconstruction. 18,20 The strength of CT is in evaluating the integrity of the osseous structure and the reconstructive hardware; 3-dimensional (3D) volume rendering provides valuable assessment for the restoration of the orbital contour and volume.…”
Section: Imaging Protocolsmentioning
confidence: 99%